Ginsenosides improve reproductive capability of aged female Drosophila through mechanism dependent on ecdysteroid receptor (ECR) and steroid signaling pathway - Fu, Baoyu; Ma, Rui; Liu, Fangbing; Chen, Xuenan; Teng, Xiaoyu; Yang, Pengdi; Liu, Jianzeng; Zhao, Daqing; Sun, Liwei (Frontiers in Endocrinology, 2022)
Aging ovaries caused diminished fertility and depleted steroid hormone level. Ginsenosides, the active ingredient in ginseng, had estrogen-like hormonal effects. Although ginsenosides were well known for their ability to alleviate many age-related degenerative diseases, the effect of ginsenosides on the decline in reproductive capability caused by aging, as well as the mechanism, are unknown. We found that ginsenoside could enhance reproductive capacity, prolong life span and restore activity, compared with aging female Drosophila. In addition, ginsenosides inhibited ovarian atrophy and maintained steroid hormone 20-Hydroxyecdysone (20E) and juvenile-preserving hormone (JH)) levels. Ginsenosides activated ecdysteroid receptor (ECR) and increased the expression of the early transcription genes E74 and Broad (Br), which triggered steroid signaling pathway. Meanwhile, ginsenosides promoted JH biosynthesis by increasing the expression of Hydroxyl-methylglutaryl-CoA reductase (HMGR) and juvenile hormone acid O-methyltransferase (JHAMT). Subsequently, JH was bound to Methoprene Tolerant (Met) and activated the transcription of the responsive gene Kruppel Homolog 1 (Kr-h1), which coordinated with 20E signaling to promote the reproduction of aged female Drosophila. The reproductive capacity and steroid hormone levels were not improved and the steroid signaling pathway was not activated in ginsenoside-treated ECR knockout Drosophila. This suggested that ginsenosides played a role dependent on targeted ECR. Furthermore, 17 kinds of ginsenoside monomers were identified from the total ginsenosides. Among them, Rg1, Re and Rb1 improved the reproductive capacity and steroid hormone levels of aged female Drosophila, which has similar effects to the total ginsenoside. These results indicated that ginsenosides could enhance the reproductive capacity of older female Drosophila by activating steroid signals dependent on nuclear receptor ECR. In addition, Rg1, Re and Rb1 in the total ginsenosides might jointly regulate reproductive function through synergistic effect. This will provide strong evidence that ginsenosides had the potential to alleviate age-induced reproductive degradation.